2013
DOI: 10.1145/2536764.2536769
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual impact of gesture control of spatialization

Abstract: In two experiments, visual cues from gesture control of spatialization were found to affect auditory movement perception depending on the identifiability of auditory motion trajectories, the congruency of audiovisual stimulation, the sensory focus of attention, and the attentional process involved. Visibility of the performer's gestures improved spatial audio trajectory identification, but it shifted the listeners' attention to vision, impairing auditory motion encoding in the case of incongruent stimulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Their results showed that increasing the number of loudspeakers improved the trajectory localization but induced a detrimental sound coloration. Finally, Marentakis and McAdams also investigated trajectory perception on a VAD but pursuing a different goal: the perceptual impact of gesture control of spatialization [31]. Their experiment compared trajectory recognition by subjects exposed to 1 -a unimodal condition (auditory stimulus alone rendered in VBAP) and 2 -a bimodal condition in which a "performer" made gestures congruent or incongruent with the sound trajectory.…”
Section: Background: Perception Of Moving Sound Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results showed that increasing the number of loudspeakers improved the trajectory localization but induced a detrimental sound coloration. Finally, Marentakis and McAdams also investigated trajectory perception on a VAD but pursuing a different goal: the perceptual impact of gesture control of spatialization [31]. Their experiment compared trajectory recognition by subjects exposed to 1 -a unimodal condition (auditory stimulus alone rendered in VBAP) and 2 -a bimodal condition in which a "performer" made gestures congruent or incongruent with the sound trajectory.…”
Section: Background: Perception Of Moving Sound Sourcesmentioning
confidence: 99%
“…The few dynamic sound localization studies we mentioned in the introduction used either a Multiple-Choice Questionnaire (MCQ) allowing allowing the subjects to choose between various fixed trajectories [31], or free 2D drawing of the trajectories [29,28]. While MCQ results are easy to analyze, this method may be too restrictive and may influence subject choices.…”
Section: User Response Interfacementioning
confidence: 99%